If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15k + -19 = 5 + -13k Reorder the terms: -19 + -15k = 5 + -13k Solving -19 + -15k = 5 + -13k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '13k' to each side of the equation. -19 + -15k + 13k = 5 + -13k + 13k Combine like terms: -15k + 13k = -2k -19 + -2k = 5 + -13k + 13k Combine like terms: -13k + 13k = 0 -19 + -2k = 5 + 0 -19 + -2k = 5 Add '19' to each side of the equation. -19 + 19 + -2k = 5 + 19 Combine like terms: -19 + 19 = 0 0 + -2k = 5 + 19 -2k = 5 + 19 Combine like terms: 5 + 19 = 24 -2k = 24 Divide each side by '-2'. k = -12 Simplifying k = -12
| x/3=(x/5)+4 | | 12=2z/-6 | | -7(n-4)-(-3n-4)=-5n | | 8x+1=7x+12 | | 1=6x-4 | | 5x+4=3+4x | | 82-2x=3x+22 | | 5x^4-20x-25=0 | | 12-4y=24 | | 8+x=3x+2 | | 22-2=5x | | 8+x=3x+12 | | 10x=6x-28 | | 5(3x-4)+2x=65 | | -12+5x=15-4x | | 4-(-x+4)=12 | | 73-5x=4x+23 | | -10=x-4 | | 11x-36=6x+34 | | 3=1.725t+t | | X/7+3=5 | | (n+4)*6=36 | | 4y+15=35 | | -3-2x=-6 | | 3x+62=7x+6 | | 2(2f-3)=4(4f-8) | | 5w^2+13w=-6 | | (2x-5)2=144 | | a/7-5=10 | | -4x+37y=0 | | 10+2a=20 | | 5(6+x)5+4=7 |